IMPLEMENTING THE HIJAIYAH LETTER RECOGNITION METHOD IN QUR'ANIC READING INSTRUCTION AT MIN MEDAN CITY - Hamka Siregar; Rusydi Ananda; Yusnaili Budianti (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to describe the implementation of the Hijaiyah letter recognition method in learning to read the Qur’an at State Islamic Elementary Schools (Madrasah Ibtidaiyah Negeri/MIN) in Medan City, as well as to analyze the obstacles encountered and its impact on improving students’ Qur’anic reading ability. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects included Qur’an–Hadith teachers, school principals, and students at MIN 1, MIN 7, and MIN 12 Medan. The findings indicate that Qur’anic reading instruction was conducted using the Iqra’ method combined with a gradual Hijaiyah letter recognition approach. This method was implemented in several stages, including the introduction of Hijaiyah letters, the introduction of vowel marks (harakat), sukun, and shaddah (tasydid), as well as manipulative exercises in arranging letters and modifying vowel signs. The results reveal that some students still experienced difficulties in recognizing Hijaiyah letters, reading connected letters, and understanding Qur’anic diacritical marks. However, after the intensive and systematic application of the Hijaiyah letter recognition method, there was a significant improvement in students’ reading fluency and confidence in reciting the Qur’an. The supporting factors for the success of this method included a structured teaching strategy, active teacher involvement, and the availability of additional guidance programs outside regular class hours. Meanwhile, the inhibiting factors consisted of limited instructional time, low learning motivation among some students, and a lack of support from the family environment. Therefore, the Hijaiyah letter recognition method can be recommended as an effective alternative approach to improving Qur’anic reading skills among students at the elementary madrasah level